2009
DOI: 10.1097/ftd.0b013e31819c33b8
|View full text |Cite
|
Sign up to set email alerts
|

Hair Analysis of Fatty Acid Ethyl Esters in the Detection of Excessive Drinking in the Context of Fetal Alcohol Spectrum Disorders

Abstract: A serious challenge in diagnosing fetal alcohol spectrum disorder (FASD) is the need to document alcohol use during pregnancy. Maternal/paternal alcohol abuse affects the likelihood of fetal alcohol exposure, and hence the occurrence of FASD. The objective of the current study was to document the use of the fatty acid ethyl ester (FAEE) hair test, a biomarker of excessive alcohol use, in parents at risk of having children with FASD and quantify the prevalence of alcohol use in this population. Hair samples sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 61 publications
0
18
0
1
Order By: Relevance
“…Kulaga and colleagues evaluated the presence of FAEEs in 324 maternal hair samples. The majority of samples (62%) had cumulative FAEEs levels above a level that excludes strict abstinence (0.2 ng/mg) and many (19%) were highly positive (above 1.0 ng/mg) [89]. The results suggest that FAEEs hair analysis may be a powerful tool in detecting excessive alcohol use in the perinatal period.…”
Section: Uplc-ms/msmentioning
confidence: 93%
See 1 more Smart Citation
“…Kulaga and colleagues evaluated the presence of FAEEs in 324 maternal hair samples. The majority of samples (62%) had cumulative FAEEs levels above a level that excludes strict abstinence (0.2 ng/mg) and many (19%) were highly positive (above 1.0 ng/mg) [89]. The results suggest that FAEEs hair analysis may be a powerful tool in detecting excessive alcohol use in the perinatal period.…”
Section: Uplc-ms/msmentioning
confidence: 93%
“…The results suggest that FAEEs hair analysis may be a powerful tool in detecting excessive alcohol use in the perinatal period. In this context, hair testing for FAEEs in 26 pregnant women disclosed a 19% positive samples for excessive drinking, with levels above the cut-off of 0.5 ng/mg [89]. However, Morini et al [90] reported that monitoring FAEEs concentration in hair of pregnant women was not useful in detecting ethanol intake lower than 30 g/day.…”
Section: Uplc-ms/msmentioning
confidence: 94%
“…Their study found a correlation between FAEE levels in hair samples and the amount of ethanol consumed even after 2 months of subsequent abstinence. Similarly, Kulaga and Koren [69] documented the use of FAEEs hair test in parents at risk of having children with FASD and quantified the prevalence of alcohol use in this population. From a total of 26 pregnant subjects whose hair was analyzed for FAEE, 19% tested positive for excessive drinking, with levels above 0.5 ng/mg.…”
Section: Use Of Faees For Diagnosis Maternal Consumptionmentioning
confidence: 97%
“…Bu amaçla kullanılan yöntemler, artmış karaciğer enzimi aktivitesi, artmış eritrosit ortalama hücre hacmi veya karbonhidrattan eksik transferrin varlığı gibi yöntemlerdir. 2,49,50 Ancak, bu göstergeler patolojik nedenleri de gösterebilmek-tedir.…”
Section: Alkolün Kötüye Kullaniminin Saptanmasiunclassified